74 Stocker management and impacts on health and subsequent feedlot performance. (29th July 2019) - Beck, Paul A; Horn, Gerald; Kegley, Elizabeth B; Powell, Jeremy G; Rivera, Daniel
Abstract: The stocker segment of the beef industry provides significant enterprise services. The stocker industry provides a shock absorber to absorb the bulk of the cattle not ready for finishing in the numbers glut in the fall and helps provide a year around supply of feeder cattle. Other benefits include adding size to small and medium frame cattle to allow them to finish at acceptable weights, grouping cattle from small herds into semiload lots, and improved health and resilience to the stressors of changing diets, management, and environment. Health during receiving to the finishing phase has been shown to impact finishing performance and carcass quality, so the effects of stocker management can have serious implications on long-term economics of the feedlot enterprise and consumer acceptance of beef products. Ratliff et al. (2014) compiled data from Arkansas receiving and stocker grazing experiments and found that calves coming into the receiving unit as bulls were more likely to experience 2nd and 3 rd pulls for bovine respiratory disease and had lower gains during grazing than calves coming in as steers. Records from research trials conducted in Mississippi and Arkansas found a 6 to 14% reduction in ADG for calves that had been treated for BRD once vs two times or more, respectively. There is much less data that considers the health outcomes of calves received as light weight stocker cattle and how this impacts subsequent performance during finishing. Timing of application of growth promoting technologies during the stocker phase has been shown to affect response to implants during finishing and carcass quality, but little data is available regarding stocker cattle health and finishing performance. More research is needed to ascertain what determines the quality of the health intervention outcomes for individual animals and the subsequent implications of health in the stocker phase